STRATEGI PENELITIAN DAN PENGEMBANGAN MENGHADAPI DINAMIKA PERKEMBANGAN LADA DUNIA / Research and Development Strategy to Face World Dynamics of Development of Pepper - Rosihan Rosman (Puslitbang Perkebunan, 2016)
Indonesia is one of the world’s main - pepper producers. Now days, Indonesian pepper experienced a fairly strong competition from other countries. Problem arising to day is low productivity and quality. Productivity of Indonesia pepper below 1000 kg/ha, whereas other countries have more than 2000 kg/ha. Low quality due to processing methods are still tradisional. Low productivity because many older plants, damaged, pests, and diseases, and lack of maintenance. To face the dynamic development of the world pepper, needed efforts to increase production, productivity and quality, so that Indonesia can improve the competitiveness in the international market. Increasing of production and quality can do the improvement of cultivation technology and post harvest. As for the necessary policy are (1) establish of research and development programs of a more site-specific and based on agro-ecological conditions, especially physical, chemical and biological characterization of soil and climate of development region, and (2) socialization result of the research and inform pepper dynamic development in the field.